Pengaruh Metode Applicative Language Teaching (ATL) Terhaadap Hasil Belajar Nahwu Pada Orang Tua Pemula di Masjid Nurul Amin Pekanbaru - Shobirin, Abdurrahman; Habibah, Amelia Nur; Azmi, Rahmanadhira; Yusup, Agung (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2024)
This research is a qualitative research to determine the urgency of the Arabic language, its objectives, materials, and learning methods for beginner parents at the Nurul Amin mosque Pandau Jaya, Riau. and also this research is a quantitative research to determine the effect of the Applicative Language Teaching method on the learning outcomes of Nahwu for beginner parents in the same place with different professions. the researchers used interviews and written tests to collect data. and they carry out selection, classification, and draw conclusions to analyze qualitative data. and they also carried out normality tests and t tests using the SPSS 25 application to analyze quantitative data. The results of the research are as follows: (1) Arabic has a very important position for every Muslim so that it is considered that this language is his identity. so they should know the urgency, objectives, basic materials, and various learning methods. and the method that is suitable for beginners is the Applicative Language Teaching method. (2) in terms of the normality test, it is known that the pre-test average is 0.130 and the post-test average is 0.594, which is greater than 0.05, so both data are normally distributed. and in terms of the t test, it is known that the calculated t value of 4.403 is greater than the t table of 2.306 and the Sig value. 2 tailed 0.03 is smaller than 0.05, so Ha is accepted and Ho is rejected, namely the Applicative language teaching method has a significant effect on the learning outcomes of Nahwu science for beginners.